Does natural environment prefer the right to the left? Governors' partisanship and corporate environmental performance. (14th February 2020) - Yu, Byungjun; Zeng, Saixing; Meng, Xiaohua; Ma, Hanyang; Sun, Daxin
Abstract: This study investigates the relationship between governors' partisanship and the corporate environmental performance of firms in South Korea. According to political ideology perspective, governors' partisanship closely influences the policy directions and preferences of the provincial administration. Conservative (red) governors tend to induce and encourage competition among firms by deregulating and offering policy benefits to businesses at the provincial level. In response to increased competition in provinces governed by red governors, firms commit to aggressive environmental initiatives as a strategic differentiation tool, in contrast to their behavior in provinces controlled by liberal (blue) governors. Moreover, we examine a contingent role of the provincial Congress. According to the principle of checks and balances, the positive impact of red governors on a firm's environmental performance is stronger when the provincial Congress is controlled by the liberal (blue) party, with its checks and balances on the red governors. This study extends an institutional theory by exploring institutional setting mechanisms at the provincial level.